The Untamed Impact of a Faraway Shock: Africa and the War in Ukraine (The Strategic Review for Southern Africa, 2022)
The combinations of multiple disruptors in the world economy have now been reinforced by the return — through the front door — of the warmongering behaviour of the great powers. This is arguably to defend geostrategic interests. The consequences for Africa are brutal. After a decade and a half of considerable progress in its macroeconomic management and social indicators, halted first by the 2008–2009 global financial crisis and now by the impact of the pandemic, the continent was at the limit of its capacity when, in February, Russian troops entered Ukraine. A finer analysis allows us to discern that Africa is simultaneously experiencing a moment of great convergence and one of divergence. The convergence is verifiable at the level of opinions and the construction of defensive positions in relation to global actors, while the divergences are related to the end of a certain notion of globalisation that is likely to deeply affect the continent. Africans’ choices in the international arena have become more limited, although that may eventually create the opportunity for a more courageous attitude.
Keywords: Russia; Ukraine; Africa; Geopolitical; War; Economy; Crises